O uso da informação no âmbito acadêmico: o comportamento informacional de pós-graduandos da área de Educação - Casarin, Helen de Castro Silva [UNESP]; Oliveira, Etiene Siqueira de [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2012)
This study reports part of a broader research about information behavior of graduate students in Education. The research´s participants were nine masters and doctoral students from a graduate program in Education at a public university. The focus group technique was used to collect the data. The focus group sessions were observed and recorded. The recorded data were transcribed, categorized and then analyzed using the technique of content analysis. The main aspects achieved were: i) Identification’s forms of information resources for research; ii) Internet as source of information; iii) Academic Library’s services and resources use; iv) Training to use of electronic data base; v) Difficulties to perform the search; vi) Advisor’s influence on research development; and vii) Environmental factors that affect information seeking behavior. The main results reveal that the identification of information sources occurs, mainly, through references quoted on studies of the researched area; as well as the advisors’ influence in the information seeking behavior of the participants. The results, also, disclose some environmental aspects, as example, lack of time to search and discomfort caused by the libraries’ environment that influenced negatively the information behavior of the studied group.

Este artigo relata parte de uma pesquisa mais ampla que teve como objetivo caracterizar o comportamento informacional dos pós-graduandos da área de Educação. Participaram da pesquisa nove alunos de mestrado e doutorado de um programa de pós-graduação em Educação de uma universidade pública paulista. Para coleta de dados, utilizou-se a técnica de grupo focal. As sessões foram observadas e gravadas e os dados registrados foram transcritos, categorizados e posteriormente analisados utilizando-se a técnica de análise de conteúdo. Foram levantados: i) Forma de identificação de recursos informacionais para pesquisa; ii) Visão da Internet como fonte de informação; iii) Utilização dos recursos e serviços da biblioteca universitária; iv)Treinamento para a utilização das bases de dados eletrônicas; v)Dificuldades para a realização da busca; vi) A influência do orientador no desenvolvimento da pesquisa; e vii) Fatores ambientais que afetam o comportamento de busca. Os principais resultados demonstraram que a identificação dos recursos informacionais ocorre, principalmente, por meio das referências bibliográficas de trabalhos da área; que há influência do orientador no comportamento de busca dos participantes. Em relação aos aspectos ambientais, verificou-se que falta de tempo para realizar as atividades de busca e o desconforto causado pelo ambiente físico das bibliotecas foram apontados como os principais fatores influenciavam negativamente o comportamento informacional do grupo estudado.
Academic use of information: the information behavior of graduate students in education
Keywords: comportamento informacional; Pós-graduandos; comportamento de busca; Educação